2009
DOI: 10.1007/s12282-009-0101-4
|View full text |Cite
|
Sign up to set email alerts
|

Intracystic invasive papillary carcinoma of the male breast with analyses of loss of heterozygosity on chromosome 16q

Abstract: A 64-year-old man noticed a right subareolar mass in May 2005. On physical examination, an oval-shaped, well-circumscribedthe tumor (6.0 x 5.5 cm in size) was located just beneath the right nipple. The tumor was elastic, firm and freely movable. Neither axillary nor supraclavicular lymph nodes were palpable. Mammography demonstrated a 5 x 5-cm, relatively distinct and dense mass without microcalcifications or spiculations. There were no findings of concurrent gynecomastia. Ultrasonography revealed a large mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…Although intra-tumoral heterogeneity may result in discordant cytogenetic profiles, this minor effect may be considered negligible when distinguishing malignant from benign samples by our 14 method. Moreover, cytogenetic profiles of five cancer cases showed 16q loss and 1q gain as the most frequently altered region, which is a typical cytogenetic profile of papillary breast carcinomas, as reported previously [16][17][18][19][20].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Although intra-tumoral heterogeneity may result in discordant cytogenetic profiles, this minor effect may be considered negligible when distinguishing malignant from benign samples by our 14 method. Moreover, cytogenetic profiles of five cancer cases showed 16q loss and 1q gain as the most frequently altered region, which is a typical cytogenetic profile of papillary breast carcinomas, as reported previously [16][17][18][19][20].…”
Section: Discussionsupporting
confidence: 80%
“…There are many reports indicating the presence of genomic alterations in intracystic papillary carcinoma of the breast [16][17][18][19][20]. We recently reported that genome-wide copy number aberrations could easily be detected by array comparative genomic hybridization (aCGH), which could then be used to quantify GIN, and that intracystic papillary carcinoma harbors significant GIN compared with intracystic papilloma [21].…”
Section: Introductionmentioning
confidence: 99%
“…There are several known genetic factors that can predispose affected individuals to increased risk of malignant transformation including chromosome 16p13 and -q21 tumor suppressor gene mutations. Loss of heterozygosity and TP53 deletions at the 16q23 locus may also play a role in the progression of intraductal papilloma to papillary carcinoma in male patients [12]. The incidence of invasive papillary carcinoma of the breast is surprisingly higher in male patients than female patients and tumors with a papillary or micropapillary growth pattern may account for as many as 75% of ductal carcinoma in situ cases in men [13].…”
Section: Discussionmentioning
confidence: 99%
“…For all 25 patients, we extracted DNA from paired samples of intraductal papillary tumor cells from CNB specimens and non-tumor cells (normal mammary glands or lymph nodes) from surgically resected specimens, as previously described [9,10]. Formalin-fixed and paraffin-embedded tissue sections, 5 to 10 μm thick, were cut using a microtome.…”
Section: Microdissection Of Paraffin-embedded Tissues and Dna Extractionmentioning
confidence: 99%
“…In a previous study, we used Southern blot analysis to examine LOH on 16q in intracystic papillary tumors using DNA isolated from frozen, paired, surgically resected samples of tumor and non-tumor tissues [7]. More recently, we reported a polymerase chain reaction (PCR)-based LOH analysis technique using DNA isolated from paraffin-embedded tumor samples [9,10]. In the study we report here, we used this PCR-based approach to assess its diagnostic utility on CNB specimens of indeterminate or suspicious intraductal papillary breast lesions.…”
Section: Introductionmentioning
confidence: 99%